2015
DOI: 10.1016/j.mce.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-dihydroxyvitamin D3 stimulates human SOST gene expression and sclerostin secretion

Abstract: Sclerostin, the SOST gene product, is a negative regulator of bone formation and a positive regulator of bone resorption. In this study, treatment of human primary osteoblasts, including cells differentiated to an osteocyte-like stage, with 1α,25-dihydroxyvitaminD3 (1,25D) resulted in the dose-dependent increased expression of SOST mRNA. A similar effect was observed in human trabecular bone samples cultured ex vivo, and in osteocyte-like cultures of differentiated SAOS2 cells. Treatment of SAOS2 cells with 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 61 publications
2
22
0
2
Order By: Relevance
“…Both daily and biweekly 1,25D increased the expression of ANK, PHOSPHO1, and MGP, whereas FGF23Ab therapy increased only ANK expression. Expression of sclerostin (SOST), an inhibitor of bone formation that impairs the differentiation and mineralization of cultured osteoblasts, is known to be increased by 1,25D . FGF23Ab and biweekly 1,25D normalized the low sclerostin expression observed in untreated Hyp mice, whereas daily 1,25D induced SOST expression to threefold above that of WT mice (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both daily and biweekly 1,25D increased the expression of ANK, PHOSPHO1, and MGP, whereas FGF23Ab therapy increased only ANK expression. Expression of sclerostin (SOST), an inhibitor of bone formation that impairs the differentiation and mineralization of cultured osteoblasts, is known to be increased by 1,25D . FGF23Ab and biweekly 1,25D normalized the low sclerostin expression observed in untreated Hyp mice, whereas daily 1,25D induced SOST expression to threefold above that of WT mice (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(16) It is possible that the improvement in mineralization seen with 1,25D or FGF23Ab therapy, (16) leads to decreased lacunar size in Hyp mice. It has been shown that 1,25D stimulates SOST expression (48) and that sclerostin stimulates perilacunar matrix resorption (49) ; therefore, it is paradoxical that the increased SOST expression in treated Hyp mice is associated with improvement in lacunar size.…”
Section: Discussionmentioning
confidence: 99%
“… Addendum – While this manuscript was in revision, a report by Wijenayaka and colleagues [27] was published that concludes that Sost is up-regulated by 1,25(OH) 2 D 3 . …”
mentioning
confidence: 99%